The Influence of Organizational Learning on Employee Competencies at PT. Semen Indonesia Unit Tonasa - Muhammad, A Fadel; Joeliaty; Muizu, Wa Ode Zusnita (PT. Maju Malaqbi Makkarana, 2025)
This study examines the influence of organizational learning on employee competencies at PT. Semen Indonesia Unit Tonasa. In the context of intense market competition and rapid technological change, fostering continuous learning has become critical for organizations to enhance workforce adaptability and innovation. Organizational learning dimensions—such as personal mastery, shared vision, team learning, mental models, and systems thinking—were analyzed for their contribution to employee competencies, including knowledge, skills, and attitudes. A quantitative approach using Structural Equation Modeling (SEM) revealed a significant positive relationship between organizational learning and competencies, with a path coefficient of 0.465 and a t-statistic of 6.434. The findings underscore the role of organizational learning in improving employee collaboration, problem-solving, and strategic thinking. However, challenges like resistance to change, unequal participation, and resource limitations were identified as barriers. Addressing these issues through leadership commitment, inclusive participation, and resource optimization can amplify the impact of learning initiatives.